Development of the system of state regulation of the metallurgical industry of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In order to create a coherent and effective system of state regulation in Kazakhstan there has been created a system of state regulation, includ-ing development and implementation of concepts, programs, current and future development plans.Metallurgy is a knowledge-based branch. The increasing complex-ity of the geological conditions of ore occurrence, the need to improve the competitiveness of the metal and its further processing into high-tech products need to be improved to ensure scientific and technological pro-duction process, increased research and development, coalescence of sci-ence and production. However, in Kazakhstan the gap between science and industry enterprises of the metallurgical branch has been increasing. To save leading position of the metallurgical industry in the economy of Kazakhstan it is necessary to increase budget funding exploratory research on priority directions.
Keywords: government regulation; metallurgical industry; competi-tive; knowledge-based products; upgrading.